2021
DOI: 10.1111/avj.13117
|View full text |Cite
|
Sign up to set email alerts
|

A survey of producer practices and reproductive performance of containment and supplementary fed ewes

Abstract: Containment feeding, where ewes are fed complete rations, is used to maintain flock numbers in periods of inadequate pasture supply. Producer practices influence both the reproductive performance of ewes and the risk of health challenges. The aim of this study was to evaluate the reproductive, feeding and health management practices of producers using containment or supplementary feeding, and quantify any associations between practice and reproductive performance. An online survey of Australian producers was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The practice of flushing ewes prior to mating can improve estrus response and ovulation rate dependent on the type of supplement and the length of time fed [42][43][44]. A range of flushing lengths were reported, which is consistent with a previous survey [45], and varied by breed. A proportion of producers, predominantly autumn and summer mated Merino producers, were uncertain or did not believe flushing was a beneficial practice.…”
Section: Discussionsupporting
confidence: 75%
“…The practice of flushing ewes prior to mating can improve estrus response and ovulation rate dependent on the type of supplement and the length of time fed [42][43][44]. A range of flushing lengths were reported, which is consistent with a previous survey [45], and varied by breed. A proportion of producers, predominantly autumn and summer mated Merino producers, were uncertain or did not believe flushing was a beneficial practice.…”
Section: Discussionsupporting
confidence: 75%
“…It remains unclear whether a reduced feeding frequency would alter fecundity for ewes fed non-cereal diets. However, cerealbased rations were the most commonly used feedstuff in Australian drought-feeding situations reported in a producer survey (Robertson et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 27 (69%) were published in 2019 and thereafter, which indicates the current increased interest in this topic. Among those recently published studies, Rivas et al [ 1 ] presented the information collected from 157 sheep farms in Spain, by means of a structured questionnaire with 150 questions related to reproduction and breeding indicators in the flocks; Robertson et al [ 2 ] reported an online survey, with 43 respondents, to assess reproductive management practices and their potential interactions within sheep flocks in Australia. With regard to goat farms, Alemayehu et al [ 3 ] surveyed 242 goat farms in Ethiopia and recorded the reproductive patterns, with the aim to assess the management practices performed in that country, whilst Niang et al [ 4 ] recorded the reproductive management details of 3138 female goats in India and reported the relevant reproductive performance outcomes.…”
Section: Introductionmentioning
confidence: 99%